Laser-modified nanocrystalline NiMoO4 as an electrode material in hybrid supercapacitors - O.M. Popovych; I.M. Budzulyak; M.M. Khemii; R.V. Ilnytskyi; L.S. Yablon; D.I. Popovych; I.I. Panko (Фізика і хімія твердого тіла, 2023)
The nanocrystalline NiMoO4 obtained as a result of hydrothermal synthesis was exposed to laser radiation with a pulse energy of 70 mJ/cm2 for 5 minutes. The phase composition and size of crystallites of the triclinic structure of NiMoO4 were determined by X-ray analysis. The average crystallite size was 18 nm for laser-irradiated nickel molybdate. Impedance analysis was used to analyze the temperature dependence of the electrical conductivity of laser-modified NiMoO4. The frequency index of the power law, determined by the nonlinear approximation method, was 0.5-0.67, which corresponds to the hopping mechanism of charge carriers. The electrochemical behavior of NiMoO4 was studied using cyclic voltammetry and galvanostatic charge/discharge testing. The laser-irradiated NiMoO4 reaches a specific capacitance of 553 F/g at a scan rate of 1 mV/s. The hybrid electrochemical system based on electrodes of modified NiMoO4 and carbon material provides high Coulombic efficiency (95%) for a significant number of charge/discharge cycles.